Economic Resilience of Dairy Farmers Amid Climate Change: An Empirical Study in Pagerjurang Village - Nugroho, Jodi Setyo; Andriyani, Nur; Affandi, Muslim (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to examine the effects of the number of dairy cows, feed costs, clean water costs, barn area, and the use of milking technology on the gross income of dairy farmers in Pagerjurang Village, Boyolali Regency, within the context of climate change impacts.Methodology: Primary data were collected through interviews with 88 dairy farmers and analyzed using the Cobb-Douglas production function estimated with the Ordinary Least Squares (OLS) method.Results: The findings show that the number of dairy cows, feed costs, and barn area have a positive and significant effect on farmers’ income. Conversely, clean water costs and the use of milking technology do not significantly affect income.Applications/Originality/Value: This study identifies the factors that play the most important role in improving farmer welfare and provides evidence that government support in increasing dairy cow ownership, expanding barn capacity, and improving feed management training is crucial for strengthening farmer resilience in facing climate change.